2011
DOI: 10.1016/j.cpr.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on impulsivity: A meta-analysis of twin, family and adoption studies

Abstract: A meta-analysis of twin, family and adoption studies was conducted to estimate the magnitude of genetic and environmental influences on impulsivity. The best fitting model for 41 key studies (58 independent samples from 14 month old infants to adults; N = 27,147) included equal proportions of variance due to genetic (0.50) and non-shared environmental (0.50) influences, with genetic effects being both additive (0.38) and non-additive (0.12). Shared environmental effects were unimportant in explaining individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 161 publications
10
114
0
3
Order By: Relevance
“…For example, animals require self-control when avoiding feeding or mating in view of a higher-ranking individual, sharing food with kin, or searching for food in a new area rather than a previously rewarding foraging site. In humans, self-control has been linked to health, economic, social, and academic achievement, and is known to be heritable (170)(171)(172). In song sparrows, a study using one of the tasks reported here found a correlation between self-control and song repertoire size, a predictor of fitness in this species (173).…”
Section: Significancementioning
confidence: 95%
“…For example, animals require self-control when avoiding feeding or mating in view of a higher-ranking individual, sharing food with kin, or searching for food in a new area rather than a previously rewarding foraging site. In humans, self-control has been linked to health, economic, social, and academic achievement, and is known to be heritable (170)(171)(172). In song sparrows, a study using one of the tasks reported here found a correlation between self-control and song repertoire size, a predictor of fitness in this species (173).…”
Section: Significancementioning
confidence: 95%
“…4 To the degree that food variety seeking is a specific aspect of a more general trait comprising the need for external stimulation or sensory-specific satiety, one might expect similarities between the degree of variety that people seek across different domains beyond food (Inman, 2001). Thus, a promising route for further exploration would be to test for relationships between food variety seeking, variety seeking in other domains, differences in satiety levels, the general desires to explore and seek novelty, and other related phenotypes, including "supertaster" ability (Bezdjian, Baker, & Tuvblad, 2011;Duffy & Bartoshuk, 2000;Helm & Landschulze, 2009;Pessemier & Handelsman, 1984). Along the same lines, the current analysis should be extended by using more refined measures of food variety seeking that not only go beyond the item level but also take relevant attributes, including nutrient content or texture, into account.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Ces endophénotypes, qui servent de média-teurs entre les gènes et les trajectoires de SUP ou de JHA, peuvent prendre la forme de comportements impulsifs. Ces comportements sont effectivement des prédicteurs établis de consommation de SUP et de participation à des JHA et ils comportent une composante génétique importante (Bezdjian et al, 2011). Le troisième objectif visait précisément à regarder si les endophénotypes associés aux différentes trajectoires sont les mêmes et s'ils sont modérés de la même manière par les facteurs de l'environnement.…”
Section: Chevauchement Au Niveau De La Composante Génétique (Objectif 2)unclassified
“…Par exemple, l'impulsivité est un facteur de risque reconnu en regard de la consommation de SUP et de la participation à des JHA. En conséquence, ce facteur de risque, lui-même hautement « héritable » (Bezdjian, Baker, & Tuvblad, 2011) devrait, selon un principe de « dosage effet », distinguer les adolescents cheminant sur des trajectoires élevées de JHA et de SUP de ceux qui cheminent sur une trajectoire élevée de JHA ou de SUP.…”
Section: Introductionunclassified